Evaluation of Hospital Information Systems using Technology Acceptance Model - Prakosa, Fajar (LPPM of STIMIK ESQ, 2018)
This study aims to evaluate the implementation Hospital Information System using Technology Acceptance Model approach, which consists of portal design variables, User Abilities and Skills, Perceived Ease of Use, Perceived Usefulness, Behavioral Intention To Use, Actual System Usage. the results showed that the hospital information system was well received by the patient. the behavior of system users can accept the technology to get ease in doing the hospital administration process.